PERMASALAHAN INTERNAL DAN EKSTERNAL RUMAH TANGGA MISKIN DALAM MENUNTASKAN PENDIDIKAN DASAR DI KABUPATEN PASAMAN - Yulia Anas; Fery Andrianus; Syon Syarid (Universitas Negeri Padang, 2016)
This Research aims to know the problems of poor household in completing basic education either internally or externally in Pasaman. By using qualitative research methods for 100 sample can conclude that the main problems of the household in completing basic education internally is as follows: 1) 53% because of the difficulty of financing schools. 2.) 40% due to the lack of motivation of the school be it from children or household, 3). 32% because the mind is not capable, 4). 17% because the value is less or ugly, 5). 13% due to help take care of the household, 6). 11% for household felt education was enough/is already better than the education of head of household, 7&8) 3% due to work as family workers and 1% as labour, 8) 2% due to illness/disability so that it could not complete their primary education. While externally is because; 1) 36% due to the influence of the environment, of which around household settlement generally has many children dropped out of school, 2) 11% because of long distances to school cause homes not being able to complete their primary education because of long distances is accompanied by large transport fare.Keywords: alleviation of primary education, the region is at risk of failure of Wajar 9 years, poor households